An observation of Madagascar Teal Anas bernieri in northwestern Madagascar - Thorstrom, Russell; Rabarisoa, Rivo G M (Wildfowl, 1996)
During one week of a survey for the endangered Madagascar Fish Eagle conducted along the coast between Mahajanga and Soalala of western Madagascar in June 1995, all mangroves that were accessible by boat were searched. In addition to one pair of Fish Eagles, a pair and a large flock of 81 Madagascar Teal were observed on a tidal mudflat in the Betsiboka River delta and another pair was sighted 15 km south flying by a Fish Eagle nest located in the mangroves of this estuary.